2017
DOI: 10.1021/acs.analchem.7b00341
|View full text |Cite
|
Sign up to set email alerts
|

DNA Linkers and Diluents for Ultrastable Gold Nanoparticle Bioconjugates in Multiplexed Assay Development

Abstract: A novel bioconjugation strategy leading to ultrastable gold nanoparticles (AuNPs), utilizing DNA linkers and diluents in place of traditional self-assembled monolayers, is reported. The protective capacity of DNA confers straightforward biomolecular attachment and multistep derivatization capabilities to these nanoparticles and, more significantly, substantially enhances their stability in demanding and complex sensing environments. The DNA/AuNPs were assembled through pH-assisted thiol-gold bonding of single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…In recent decades, intensive research has been undertaken to develop new synthesis leading to ultrastable GNP. An exhaustive review of highly-stable and ultrastable GNPs led to only a dozen publications describing new synthesis conditions and resistance against different criteria [11,12,13,14,15,16,17,18,19,20,21,22]. However, most of the time, GNPs presented ultrastable properties only under limited conditions and were not water-soluble.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, intensive research has been undertaken to develop new synthesis leading to ultrastable GNP. An exhaustive review of highly-stable and ultrastable GNPs led to only a dozen publications describing new synthesis conditions and resistance against different criteria [11,12,13,14,15,16,17,18,19,20,21,22]. However, most of the time, GNPs presented ultrastable properties only under limited conditions and were not water-soluble.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, numerous GNPs have been reported to be stable for more than six months at room temperature without any alteration [18,23], but this feature should not be sufficient to define them as ultrastable [12,16,20]. The notion of time must be taken into account and the stability kinetics explained when the aggregation is observed after a few minutes following salt exposure [11,13,16,17,19,20]. Nonetheless, some studies have suggested a degree of stability against freeze drying, salts resistance [11,13,15,16,17] and/or autoclaving [24].…”
Section: Introductionmentioning
confidence: 99%
“…Binding patterns for cholera toxin are strong and specific, with signal intensities comparable to established SPR sensors in the literature. 25,26 …”
mentioning
confidence: 99%
“…Cheng's group developed a very stable conjugate using DNA as a linker on the surface of gold nanoparticles, applied to the sandwich assay to detect cholera toxin (Figure 7a) 46 . In the proposed method, DNA linker on the surface of gold nanoparticles replaced the alkanethiol/PEG linker used in the synthesis of gold nanoparticle conjugates, which helps the conjugate be stable in a complex sensing environment, improving the detected signal.…”
Section: Use Of Dna As Signal Amplifiers In Poct Immunosensorsmentioning
confidence: 99%